STUDI UPAYA PENGOPTIMALAN PENGGUNAAN BRT TRANS PATRIOT KOTA BEKASI BERDASARKAN PREFERENSI MASYARAKAT - Caroline Fadhillah Agnestina Hartono; Aleksander Purba; Shahnaz Nabila Fuady (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
Rapid population growth is able to bring significant changes to various systems of urban community activities, with the high standard of living of the community, the higher the movement carried out. The existence of high community movement must be balanced with the provision of adequate transportation facilities and infrastructure, such as the provision of good public transportation to be able to reduce private vehicles. Public transportation is able as a solution to urban transportation problems that are able to serve the community in meeting their needs for movement. The city of Bekasi as one of the buffer cities of DKI Jakarta and as one of the metropolitan cities in Indonesia has also developed BRT as a mode of urban public transportation. In 2019 Bekasi City has integrated mass public transportation, BRT Trans Patriot. However, the number of users of this public transport is low. BRT Trans Patriot is still not used optimally by the community. Based on these problems, it is necessary to study the optimization of the use of the BRT Trans Patriot based on people's preferences. The results show that service quality affects people to use Trans Patriot BRT, and it is found that the available services are not optimal in accordance with bus rapid transit standards. Regarding this, it affects the number of Trans Patriot BRT users that are not optimal.